'A Reformer's Wife ought to be an Heroine': Gender, Family and English Radicals Imprisoned under the Suspension of Habeas Corpus Act of 1817. Issue 345 (April 2016) - NAVICKAS, KATRINA
Abstract: In 1817, the British government reacted to the rise of popular agitation for parliamentary reform by passing the Suspension of Habeas Corpus Act and arresting the leaders of the new working‐class radical societies. The imprisonment of these men was a severe blow to the democratic movement. Despite the recent revival of scholarly interest in early nineteenth‐century popular politics, historians have treated the events of 1817 as a brief interlude before the better‐known Peterloo Massacre of 1819. This article argues that the development of the post‐war democratic movement cannot be understood without examining the impact of the imprisonments on the radical leaders and their families. It analyses a previously unstudied series of letters confiscated from the radical prisoners and kept in the Home Office files. The correspondence demonstrates the essential role of letter‐writing within radical culture, and how radical thought and self‐expression were mediated through the pressures of both government surveillance and financial difficulty. This article secondly offers new evidence about the gender politics of radicalism in this period. It shows how women's experience of separation from their husbands, and male attitudes towards their role in 1817–18 crucially shaped the emergence of female radicalism in public for the first time in 1819.